The Influence of Work Motivation and Work Discipline on Teacher Performance: A Quantitative Study in Junior High Schools in East Pekalongan District Pekalongan City - Arbiyanti, Dwiani; Abdullah, Ghufron; Soedjono, Soedjono (Journal of Educational Sciences, 2025)
Improving teacher performance is a major priority in strengthening the quality of education. Two important factors influencing performance are work motivation, which provides the internal drive to achieve goals, and work discipline, which ensures consistency and accountability in carrying out professional duties. Examining these factors is particularly relevant in the socio-cultural context of East Pekalongan District, Pekalongan City. This study aims to analyze the influence of work motivation and work discipline on the performance of public junior high school teachers in East Pekalongan District. The research employed a quantitative approach with an ex post facto and associative design. A total of 115 teachers were selected through proportional random sampling. Data were collected using a validated and reliable Likert-scale questionnaire, and analyzed through descriptive statistics, classical assumption testing, and multiple linear regression. The results show that work motivation has a significant positive effect on teacher performance, contributing 61.4%. Work discipline also significantly affects performance, with a contribution of 43.2%. Simultaneously, both factors explain 61.8% of the variance in teacher performance, indicating a strong combined influence. The study concludes that strengthening teacher motivation and discipline is essential for improving professional performance and suggests that schools and policymakers develop integrated strategies to optimize these two aspects.